ORGANIZATION OF THE PROCESS OF SPIRITUAL VALUES EDUCATION AMONG STUDENTS DURING CAMP THEMATIC TERM - V. Lappo (Borys Grinchenko Kyiv Metropolitan University, 2017)
The article deals with the problem of improving the forms of organization of the process of spiritual values education among students during the camp thematic term. Formation of spiritual values of student's personality is an important way of improving psychological and pedagogical process of professional training, which creates conditions for every specialist to have active life position, commitment to duty, courage, determination, responsibility, and decency and honesty in relationships between people, understanding of social importance of their activity in different situations. The author presents important issues of self-improvement of higher school students. The pedagogical factors create a thematic term in a student camp. The article states that the student camp should be focused on improving the system of personal spiritual values. Scientists suggest a thematic term programme "School for Spiritual Growth". The following programme identifies the stages of implementation. The author tells about the importance of spiritual and moral education. It is necessary for the development of personal qualities, revealing the creative potential and the formation of an active vital position of students